Observing ozone chemistry in an occupied residence - Liu, YingJun; Misztal, Pawel K.; Arata, Caleb; Weschler, Charles J; Nazaroff, William W.; Goldstein, Allen H (Proceedings of the National Academy of Sciences, 2021)
It has been suggested that indoor exposure to ozone oxidation products contributes materially to the apparent associations between outdoor ozone concentration and morbidity and mortality. Our current understanding of indoor ozone chemistry derives mainly from studies with test surfaces under controlled conditions. Little is known about the overall impact of ozone chemistry on air composition in dynamically changing indoor residential environments. The results presented here reflect a quantitative characterization of overall indoor ozone chemistry in a normally occupied home. Findings reveal a strong influence of off-body skin lipids on indoor ozone chemistry. Being able to elucidate indoor air pollutants derived from ozone chemistry facilitates the investigation of causal links between outdoor ozone concentrations and adverse health effects.Outdoor ozone transported indoors initiates oxidative chemistry, forming volatile organic products. The influence of ozone chemistry on indoor air composition has not been directly quantified in normally occupied residences. Here, we explore indoor ozone chemistry in a house in California with two adult inhabitants. We utilize space- and time-resolved measurements of ozone and volatile organic compounds (VOCs) acquired over an 8-wk summer campaign. Despite overall low indoor ozone concentrations (mean value of 4.3 ppb) and a relatively low indoor ozone decay constant (1.3 h−1), we identified multiple VOCs exhibiting clear contributions from ozone-initiated chemistry indoors. These chemicals include 6-methyl-5-hepten-2-one (6-MHO), 4-oxopentanal (4-OPA), nonenal, and C8-C12 saturated aldehydes, which are among the commonly reported products from laboratory studies of ozone interactions with indoor surfaces and with human skin lipids. These VOCs together accounted for ≥12% molecular yield with respect to house-wide consumed ozone, with the highest net product yield for nonanal (≥3.5%), followed by 6-MHO (2.7%) and 4-OPA (2.6%). Although 6-MHO and 4-OPA are prominent ozonolysis products of skin lipids (specifically squalene), ozone reaction with the body envelopes of the two occupants in this house are insufficient to explain the observed yields. Relatedly, we observed that ozone-driven chemistry continued to produce 6-MHO and 4-OPA even after the occupants had been away from the house for 5 d. These observations provide evidence that skin lipids transferred to indoor surfaces made substantial contributions to ozone reactivity in the studied house.All study data are included in the article and supporting information.